2016
DOI: 10.1002/hfm.20678
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Latent Semantics of Haptic Interaction Research: A Systematic Literature Review of Haptic Interaction Using Content Analysis and Network Analysis

Abstract: As interest in multimodal and tangible interfaces is increasing in the field of human–robot interaction and virtual reality, haptics has been researched across areas such as engineering, computer science, psychology, and neuroscience. The main objective of the study was to construct a comprehensive review of the current haptic‐related literature based on quantitative data derived from content analysis and network analysis. Using the results of content analysis and network analysis of 6,000 research articles on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…Most studies are focused on either technical aspects of implementation and display of haptics or cognitive mechanisms for users. The authors of [122] suggest to combine the two approaches to make the commercialization of applications more feasible. Although research has shown there is a need for force and tactile feedback in robotic surgery, the need is not yet addressed in any commercially available solution or products [12].…”
Section: Effect Of Haptic Feedback On Performancementioning
confidence: 99%
“…Most studies are focused on either technical aspects of implementation and display of haptics or cognitive mechanisms for users. The authors of [122] suggest to combine the two approaches to make the commercialization of applications more feasible. Although research has shown there is a need for force and tactile feedback in robotic surgery, the need is not yet addressed in any commercially available solution or products [12].…”
Section: Effect Of Haptic Feedback On Performancementioning
confidence: 99%
“…Among the possible feedback modalities available on mobile and wearable devices, haptic feedback enables a wide range of possible implementations that target various receptors on the human body-in the form of tactile, thermal, or force feedback (Basdogan, Giraud, Levesque, and Choi, 2020;Jones, 2016;Kang and Lee, 2018;Song, Lim, and Yun, 2016;Wang, Guo, Liu, Zhang, Xu, and Xiao, 2019;Youn, Lee, Kim, Shim, Chan, and Lee, 2021)-and has been found effective for contexts of use characterized by constraints such as those enumerate above. Vibrotactile feedback, which falls under the general category of haptics, is implemented via controlled vibrations targeting specific cutaneous mechanoreceptors located in the human skin.…”
Section: Introductionmentioning
confidence: 99%
“…Research related to the haptic interface may be classified as (i) studies carried out on technologies providing haptic stimuli and (ii) studies on how users perceive the haptic stimuli. The significance of human perception of haptic stimuli and the effect of emotional and psychological aspects on haptic feedback were addressed in [16]. For example, to create a sense of tactile realness, the joysticks used in the gaming industry provide vibrations in highly tense circumstances [6].…”
Section: Introductionmentioning
confidence: 99%
“…For example, to create a sense of tactile realness, the joysticks used in the gaming industry provide vibrations in highly tense circumstances [6]. The efficiency, performance, and advancement of haptic interfaces depend on the type of feedback, maneuverability, and manipulability of the end-effector, haptic stimulation, and actuator technology [16]. One of the drawbacks in the design of haptic interfaces is limited workspace and low dexterity.…”
Section: Introductionmentioning
confidence: 99%